GIS-based compactness measurement of urban form at neighborhood scale: The case of Dhaka, Bangladesh - Md Hamidur Rahman; Md Hedaetul Islam; Meher Nigar Neema (Journal of Urban Management, 2022)
Compact development is broadly professed for making significant contributions to achieve sustainable growth of cities. Therefore, evaluation of the existing compactness of urban areas is crucial for guiding future urban development. Previous studies measured urban areas' compactness at a city or metropolitan scale in a developed country context. Hence, a considerable research gap exists in studying compactness at the neighborhood scale, especially in urban areas from a developing country. This paper aims to evaluate and compare compactness level of neighborhoods in the GIS environment through broadly six indicators-population density, evenness of development, clustering nature of development, land-use diversity, floor use mix, and road network connectivity in eight neighborhoods of Dhaka city, Bangladesh. For this, the study developed a Composite Compactness Index (CCI) based on a multi-criteria decision-making (MCDM) approach. Study results classified four neighborhood as low compact, three as moderately compact, and one as high compact neighborhood. Travel behavior analysis through modal share, travel time, and travel distance validated compact neighborhoods' tenability. Here, identified low and moderate compact neighborhoods require immediate planning interventions for improving their compactness level. Results from this study can work as a preliminary guideline for planners, policymakers, and development agencies for designing a more sustainable and efficient urban form through compact urban development on neighborhood scale. The developed methodology presented here can be applied to other areas with refinements necessary for corresponding geographic location.
Keywords: 710; Compactness index; Dhaka; MCDM; Neighborhood; Urban form